P97 Quantifying the Return on Investment of Public Health Interventions: A systematic review. (13th September 2016) - Mason, R; Anwar, E; Collins, B; Cookson, R; Capewell, S; Lloyd-Williams, F
Abstract : Background: Benjamin Franklin once famously stated that "an ounce of prevention is worth a pound of cure". Despite this concept, the Treasury recently announced substantial cuts to the public health budget. Ignoring previous assurances that no service cuts would be made. A number of organisations have suggested that cuts to public health budgets are a short sighted false economy, and will likely lead to considerable harms. To help inform the potential impact of cuts to public health budgets, we set out to determine the return on investment (ROI) and opportunity cost for a range of public health interventions. We further hypothesised a "public health Effectiveness Hierarchy": that the median ROI of interventions delivered at a national level is at least a twofold greater than those delivered at regional or local level. Methods: We conducted systematic searches on all relevant databases (including MEDLINE; EMBASE; CINAHL; AMED) to identify studies that calculated or reported a return on investment for public health interventions in the UK and other countries where relevant. Interventions were stratified by national, regional and local level to test the effectiveness hierarchy hypothesis. Results: We identified 5020 potentially relevant titles, and finally included 52. Many studies examined 'health protection' interventions such as vaccination, few reported 'wider determinants' interventions. Median ROI results were 14.3 for every 1 unit invested. Studies reporting a cost benefit ratio (CBR) produced a very similar median of 14.1: 1. Stratification by level revealed an effectiveness hierarchy whereby national programmes tended to provide larger returns compared to regional or local interventions, median ROI of 28.6 versus 4.0, median CBR 17.5 versus 10.3. The quality and analysis of ROI values ranged widely, but was generally better in studies reporting a CBR. Conclusion: Extensive evidence suggests that Benjamin Franklin was correct – public health interventions offer substantial returns on investment. Nation-wide programmes typically achieved returns on investment averaging 14:1 compared with 4:1 returns for local interventions, consistent with a public health effectiveness hierarchy. The proposed Treasury cuts to local public health budgets in England might therefore be a false economy. The so-called "efficiency savings" will paradoxically result in substantial additional costs to the NHS and the wider economy.